Charged-particle multiplicity density at midrapidity in central Pb-Pb collisions at √sNN=2.76 TeV - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; Schicker, Rainer; Schweda, Kai; et al. (Physical review letters, 2010)
The first measurement of the charged-particle multiplicity density at midrapidity in Pb-Pb collisions at a center-of-mass energy per nucleon pair √sNN=2.76 TeV is presented. For an event sample corresponding to the most central 5% of the hadronic cross section, the pseudorapidity density of primary charged particles at midrapidity is 1584±4(stat)±76(syst), which corresponds to 8.3±0.4(syst) per participating nucleon pair. This represents an increase of about a factor 1.9 relative to pp collisions at similar collision energies, and about a factor 2.2 to central Au-Au collisions at √sNN=0.2 TeV. This measurement provides the first experimental constraint for models of nucleus-nucleus collisions at LHC energies.
*(ALICE Collaboration): K. Aamodt, V. Anguelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, J. Mercado Pérez, K. Oyama, Y. Pachmayer, R. Schicker, K. Schweda, J. Stachel, S. Vallero, B. Windelband [und 952 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Im Titel ist der Buchstabe s hochgestellt
Gesehen am 14.11.2022